PS-007 Survey on the use of vials and pens as insulin delivery devices in hospitalisation units. (24th March 2015) - Lara, C; Ruano, M; Villamañán, E; Pérez, E; Balade, L; Herrero, A
Abstract : Background: Insulin is a high-risk drug not always used properly in hospitals according to the current recommendations. Purpose: To find out what is the usual practice in use and storage of different types of insulin delivery devices (vials-pens) in hospital. Material and methods: Pharmacists surveyed nurses in non-critical wards concerning safety, handling and storage conditions of insulin in a general hospital (420 adult beds). Results: A total of 77 questionnaires were returned. Concerning safety, vials were used for several patients (100%). Pens were generally used in the right way, however some nurses (32.5%) admitted using them occasionally for different patients, taking out doses with a syringe. Dispensing sealed pens from the pharmacy was considered an effective safety measure (92%). In terms of handling the vials, 83% of nurses used them with safety insulin syringes. Pens were used with conventional, non-safety needles (100%), without purging in 52% of cases and 80% removed the needle from the pen after administration. About how the needle was removed: 39% unscrewed it directly to discard it, 35% covered it first with the outside protector and 14% with the inside one. At discharge 50% delivered an opened pen to the patient; otherwise, the pens were left in the unit's medicines storage area or discarded. Opened pens and vials were stored in the unit's medicines storage area, mostly in the refrigerator (67% and 57%, respectively). Lack of specific training was detected when the patient was isolated (no response in 35%). Insulin vials were only identified with the opening date (71.5%). 70% of nurses identified opened pens with the patient identification label and also 12% with the opening date. Conclusion: Nursing staff are generally familiar with the safe handling and storage of insulin delivery devices, although we found a high variability in some of their responses. Publishing recommendations by the Pharmacy Department in this regard would be helpful to reach a greater uniformity in the practice. References and/or acknowledgements: Nursing No conflict of interest.